Impact of Emotional Intelligence and Self-Efficacy on Self-Esteem Among Nursing Students (International Journal of Nursing Education, 2026)
Introduction: Nursing is a profession that demands not only clinical competence but also strong emotional andpsychological adaptability. Objectives of the study were to correlate the level of emotional intelligence and self-efficacyon self-esteem and to associate the level of emotional intelligence, self-efficacy, and self-esteem with their selectedsociodemographic variables.Methods: Descriptive cross-sectional research design was used for the research. 289 samples were taken using thecomplete enumerative sampling technique. The Rosenberg Self-Esteem Scale, the General Self-Efficacy Scale, and theSchutte Self-Report Emotional Intelligence Test (SSEIT) were the tools of the study. The data gathered at the selectednursing college was analyzed by descriptive and inferential statistical methods, and interpretations were madebased on the objectives of the study.Results: The study results show that a moderate positive correlation between emotional intelligence and self-esteemwas observed with r = 0.64; on the other hand, a strong positive correlation of r = 0.97 was observed for self-efficacy &self-esteem. Association of the demographic variables revealed that age, course, year of the study, and religion wereassociated with emotional intelligence at chi-square 0.0270, 0.0038, and 0.0417, respectively, at p < 0.5 level at 95% CI.Conclusion: The study emphasizes that emotional intelligence, self-esteem, and self-efficacy are interrelated constructsinfluencing one another and that certain demographic factors play a significant role in shaping emotional intelligenceamong the participants. Promoting emotional intelligence and self-efficacy through targeted educational andpsychological interventions may therefore enhance students’ overall self-esteem and personal growth.
Keywords: emotional intelligence,self-efficacy,self-esteem,nursing students